Improving Speaking English Ability Using Role Play Method for Elementary Students - Arum Putri Rahayu (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2022)
This study aims to help improve students' ability to speak in English, so a researcher used Role Play method with students being able to explore their ability to speak English, increase their desire to speak English and English vocabulary for SDN Girimulyo I students in communicating with good English and build students to learn English, Especially in speaking aspect. This research is a class action research using two cycles, namely, cycle I and cycle II. The results showed that the average score of their speaking skills increased from cycle I to cycle II. The results showed that the average score of their speaking skills increased from cycle I to cycle II. This was shown by the Spelling results in cycle I (43.25%) to (85.2%) in cycle II. Students' mastery of the fluency aspect in cycle I (51.2%) to (79.1%) in cycle II. Pronunciation aspect of cycle I (56%) to (80.2%) in cycle II. The vocabulary aspect in cycle I (37.5%) became (80.1%) in cycle II. Comprehension increased from cycle I (45.3%) to (79.05%). The conclusion obtained is that role play is proven to improve students' speaking skills. The role play method gives students many opportunities to practice and practice directly.